Conversion of Glycerol to Poly(3-Hydroxypropionate) in Recombinant Escherichia coli - Andreeßen, Björn (American Society for Microbiology (ASM), 2010)
We have developed the conversion of glycerol into thermoplastic poly(3-hydroxypropionate) [poly(3HP)]. For this, the genes for glycerol dehydratase (dhaB1) of Clostridium butyricum, propionaldehyde dehydrogenase (pduP) of Salmonella enterica serovar Typhimurium LT2, and polyhydroxyalkanoate (PHA) synthase (phaC1) of Ralstonia eutropha were expressed in recombinant Escherichia coli. Poly(3HP) was accumulated up to 11.98% (wt/wt [cell dry weight]) in a two-step, fed-batch fermentation. The present study shows an interesting application to engineer a poly(3HP) synthesis pathway in bacteria.